Dampak gadget terhadap aspek perkembangan anak di Dusun Sumbergong - Sa’diyah, Siti Khalimatus (Maliki Interdisciplinary Journal, 2024)
Gadgets are sophisticated technologies or devices that can be used as communication tools, learning tools, work, and play. The use of gadgets will have a positive impact on children, it can also have a negative impact if the use of gadgets is not limited and not used properly. The use of these gadgets will also affect aspects of child development. The purpose of this study was to find out the impact of the use of gadgets on aspects of children’s development in Sumbergong Hamlet, Kedok Village, Turen District, Malang Regency. This research method uses qualitative research methods with the target research subjects of Sumbergong Hamlet children aged 6-10 years. The results of the study stated that the use of gadgets in the long term can affect aspects of child development in Sumbergong Hamlet.